2012
DOI: 10.1111/j.1574-6968.2011.02490.x
|View full text |Cite
|
Sign up to set email alerts
|

A d-octapeptide drug efflux pump inhibitor acts synergistically with azoles in a murine oral candidiasis infection model

Abstract: Clinical management of patients undergoing treatment of oropharyngeal candidiasis with azole antifungals can be impaired by azole resistance. High-level azole resistance is often caused by the overexpression of Candida albicans efflux pump Cdr1p. Inhibition of this pump therefore represents a target for combination therapies that reverse azole resistance. We assessed the therapeutic potential of the D-octapeptide derivative RC21v3, a Cdr1p inhibitor, in the treatment of murine oral candidiasis caused by either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 25 publications
0
27
0
2
Order By: Relevance
“…The inhibitors for ABC pumps such as milbemycins, enniatin, FK506, FK520, and unnarmicins can be used along with azole drugs to reverse the drug resistance [73, 156159]. Recently, Hayama et al have assessed the therapeutic potential of D-octapeptide derivative RC21v3 (an inhibitor of Cdr1p) in a murine oral candidiasis infection model and have shown its potential in combination with fluconazole [160]. This suggests that this inhibitor has a potential in treating oral candidiasis.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitors for ABC pumps such as milbemycins, enniatin, FK506, FK520, and unnarmicins can be used along with azole drugs to reverse the drug resistance [73, 156159]. Recently, Hayama et al have assessed the therapeutic potential of D-octapeptide derivative RC21v3 (an inhibitor of Cdr1p) in a murine oral candidiasis infection model and have shown its potential in combination with fluconazole [160]. This suggests that this inhibitor has a potential in treating oral candidiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Although predisposing factors, such as xerostomia and estrogen administration, have been used for inducing oral candidiasis in mice, most studies have been performed in immunosuppressed mice models 37 , 41 , 43 , 62 - 68 . Takakura et al 37 developed a murine model for experimental candidiasis that combines immunosuppression and treatment with tetracycline for successful disease progression, allowing the study of fungal pathogenesis and new therapeutic options.…”
Section: Models Of Experimental Oral Candidiasis In Micementioning
confidence: 99%
“…Using a mouse model of lethal infection, it was demonstrated that concomitant administration of the lactoferricin-derived peptide P2-15 and erythromycin against P. aeruginosa afforded long-lasting protection to one-third of the animals [180]. A d-octapeptide EPI acts synergistically with azoles in a murine oral candidiasis infection model [181]. In a latest in vivo study, PDT employing EPIs was able to reduce bacterial load in P. aeruginosa burn wounds, to delay bacteremia and to keep the bacterial levels in blood 2-3 log 10 lower compared to an untreated group [182].…”
Section: Introductionmentioning
confidence: 99%